Deep eutectic solvent (DES) pretreatment and lignin regeneration for the development of a bamboo leaf-based bioplastic - Liu, Chao; Liu, Hongfei; Wang, Huijie; Yu, Zhaochuan; Yan, Ming; Zhou, Xuelian; Li, Renai (Frontiers in Bioengineering and Biotechnology, 2024)
Abstract：The excessive utilization of petroleum-based plastic products has led to a pervasive environmental and human health threat. In response, the adoption of bioplastics derived from biomass has emerged as the foremost alternative to conventional plastics, owing to their inherent biodegradability and sustainability. The present study demonstrates the preparation of a biodegradable and cost-effective lignocellulosic bioplastic by utilizing dissolving bamboo leaf powder with deep eutectic solvents (DES) and regenerating lignin in situ. The DES was synthesized through a one-step heating and stirring method using choline chloride (ChCl) and anhydrous oxalic acid. The crystallinity of the bioplastics is enhanced by DES pretreatment, thereby improving the internal structural order of the material. Moreover, lignin regeneration reduces the pore size within the bioplastics and contributes to a more compact internal structure.The prepared lignocellulosic bioplastics exhibit remarkable mechanical strength, with a tensile strength of 113 MPa. Additionally, they demonstrate good water stability, as evidenced by a contact angle of 55.52°. Moreover, these bioplastics possess an exceptional biodegradability with a degradation rate exceeding 98% after 60 days. This study presents an innovative approach for the high-value utilization of bamboo leaf resources.